Differences in Gestational Diabetes by Migrant Status in Marche Region, 2013 – 2020. A Population-Based Study from THE MIGHTY PROJECT (CUP P2022ASXKR) (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionGestational Diabetes (GD), defined as glucose intolerance first detected during pregnancy [1], is a common complication of pregnancy which impacts both maternal and child’s health. Monitoring and characterizing its occurrence, particularly in high-risk groups, can guide GD prevention and reduce the burden of the disease.ObjectiveThe study aimed to compare the risk of Gestational Diabetes between Migrant and Italian women at their first pregnancy during 2013 and 2020 in the Marche Region.MethodsThis population-based study was based on the healthcare utilization databases of Marche Region. Using the Certificates of Delivery Assistance database (CeDAP), a cohort of women at their first singleton delivery during 2013-2020, aged 15 to 50 years at delivery, was selected. Women with at least one diabetes-related event during the year before pregnancy or within the 12th gestational week (gw), defined as glucose-lowering drug prescription (Drug prescriptions database: ATC A10*), hospitalization with a primary/secondary diagnosis of diabetes (Hospital Discharge database: ICD-9-CM 250.*), diabetes exemption (Exemption database: code 013*), or residing in the Region for less than 1 year before pregnancy (Regional Beneficiary Database), with pregnancy terminating before the 20th gw (CeDAP), were excluded.Women with GD were defined as those with an hospitalization for diabetes (Hospital Discharge: ICD-9-CM 250.*, 648.8*), or ≥1 glucose-lowering drug prescription, or included in an educational program for people with diabetes and obesity (Outpatients care database 93.82.1, 93.82.2), or an exemption for GD/diabetes (code 013*, RM013T) activated during pregnancy [2]. To detect women not traced for diabetes in healthcare services during pregnancy, those undergoing at least an OGTT or HbA1c control (Outpatients care database 92.26.4, 90.26.5, 90.28.1), or prescription for glucose-lowering drugs, within one year from delivery, were considered to have GD.Women were classified as Italians or Migrants from High Migratory Pressure Countries, HMPC [3] based on their citizenship. The HMPC group was distinguished according to the geographical area: East Europe, Africa, West-Center-South Asia, East Asia and Latin America.Adherence to the recommended AnteNatal Care (ANC) was assessed in terms of promptness and appropriateness of the number and timing of ANC, including gynaecological visits (1st visit within the 12th gw, at least 4 visits during pregnancy), ultrasounds (at least 2 examinations during pregnancy), and laboratory tests (tests appropriately performed during the pregnancy trimesters [4]). Information was retrieved from the outpatient care database. The cumulative number of ANC recommendations followed during the pregnancy was also evaluated.The association between GD and citizenship was evaluated using a multiple logistic regression adjusted for age (≥35 vs.